A new indazole-based colorimetric chemosensor for sequential detection of Cu2+ and GSH in aqueous solution. Issue 32 (10th August 2017) - Kim, Min Seon; Jung, Jae Min; Kang, Ji Hye; Ahn, Hye Mi; Kim, Pan-Gi; Kim, Cheal
Abstract: A new selective and sensitive colorimetric chemosensor1 was developed for the sequential detection of Cu 2+ and glutathione (GSH) in aqueous solution. The sensor1 detected Cu 2+ ion by an obvious color change from colorless to pale yellow. Importantly, 1 could be used to detect and quantify Cu 2+ ion in water samples, and the detection limit (0.14 μM) of1 for Cu 2+ was much lower than the guideline (31.5 μM) of WHO in drinking water. Also, Cu 2+ -2·1 complex can be used as a colorimetric sensor for GSH via naked-eye. The detection limit for GSH was founded to be 2.98 μM. Moreover, the sensing ability of1 for Cu 2+ was supported by theoretical calculations. Graphical abstract: Highlights: A new indazole-based chemosensor1 was developed for sequential detection of Cu 2+ and GSH. Sensor1 could detect Cu 2+ from colorless to pale yellow via naked-eye. Sensor1 could be used to quantify Cu 2+ ion in water samples with the low detection limit (0.14 μM). The resulting Cu 2+ -2·1 complex could be used as a colorimetric sensor for GSH.